PELATIHAN USIA LANJUT AGAR BEBAS NYERI LUTUT DI KELURAHAN PANDEAN LAMPER KECAMATAN GAYAMSARI - Metta Christiana; Ahmad Muhaimin; Wahyu Puspitasari (Program Studi Ilmu Keolahragaan, 2023)
Pandean Lamper Village is one of the villages in Gayamsari District, Semarang. About 30% of people over the age of 50 experience knee pain. The condition of the residents who experience knee pain is that most of them are not overweight, only a small number of them are indeed fat but not very fat. The activities of pre-elderly and elderly residents in Pandean Lamper Village are still active and some are still very active in carrying out daily activities such as working, organizing, shopping, cooking, cleaning the house, picking up grandchildren and so on. So even though most of them are not fat and are still active, as many as 30% are still found to have knee pain. The purpose of this activity is that pre-elderly and elderly citizens are free from knee pain. The solution to achieving this goal is to provide counseling about the importance of strengthening leg muscles and provide training in movements to strengthen leg muscles, so they can practice independently at home. The method used is exposure using a projector, video shows and simple props. After that, there is training in movements to strengthen the supporting muscles of the knee, accompanied by music to make it more fun. The result of this activity is that the participants come to know and they feel for themselves that the movements being taught do not make the knee more painful, on the contrary, it makes the knee more comfortable. It was very important to socialize this activity more broadly because it turned out that all the participants, including the Village Health Forum Management, PKK, Posyandu, did not know at all about the importance of muscle strength to help reduce pressure on the knees.